The Characteristics Of The Ideal Lecturer From The Female Students' Perspective And The Relationship Of These Characteristics With Student’s Motivation Towards Learning - Khalid Waleed Nofan Askar (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This research aims to determine the characteristics of ideal lecturers at the College of Education for Girls (from a student's perspective) and the relationship between these characteristics and student motivation to learn. This research included three hypotheses and was applied to students at the College of Education for Girls - Tikrit University. Researchers relied on an ideal lecturer characteristics scale (from the student's perspective) and a learning motivation scale, both of which were developed electronically, using a correlational descriptive approach. The sample consisted of 190 students, and the sample was selected using a quasi-random method. Several statistical methods are used to process the results obtained by researchers. After obtaining and discussing the results, several conclusions were obtained which can be summarized as follows: Positive lecturer personality traits increase student-teacher interaction and make a significant contribution to the success of the educational process. Apart from that, students' motivation in studying the subjects they study is influenced by the personal qualities of their lecturers. The study resulted in a series of recommendations: (i) updating ongoing professional development courses for all lecturers to provide them with the psychological and educational foundation necessary to ensure that their interactions with students are based not only on academic merit and grades, but also on an understanding of personality student. (ii) diagnose students with high and low academic achievement motivation. Based on this diagnosis, lecturers must be able to adjust their teaching methods and interactions with students.